Imperial hubris : why the West is losing the war on terror (Brassey's, 2004)
An anonymous member of the U.S. intelligence community maintains that we are, in fact, losing the war on terror. Although aspects of the modern world may offend conservative Muslims, no Islamist leader has fomented jihad to destroy Western institutions. Rather, a growing segment of the Islamic world disapproves of specific U.S. policies and their attendant military, political, and economic implications. Osama bin Laden articulates a consistent and convincing case that Islam is under attack by America. "Anonymous" contends Al Qaeda seeks not to destroy our secular, democratic way of life, but to deter what they view as specific attacks on their lands, their communities, and their religion. Unless U.S. leaders recognize this fact and adjust their policies accordingly, even moderate Muslims will join the bin Laden camp.